Understanding Hong Kong students’ intercultural behavior: an approach using the theory of planned behavior - Kerry J. Kennedy; Jinxin Zhu (Cogent Education)
Intercultural competence is a key skill for the 21st century on account of increasing mobility, contentious politics and increasing international tensions. Yet particularly in Asian contexts there is a question about young people’s readiness and capacity. PISA’s study of global competence took up this issue using samples of students from 27 societies. This paper explores Hong Kong, where intercultural issues are complex and often misunderstood. Respect for People from Other Cultures (RPOC) was adopted as the outcome measure located within an hypothesized model consisting of factors affecting students’ behavioral aspects of intercultural competence. The sample was drawn from the PISA database with a two-level path analysis used to analyse the data. The results indicated that students’ interest in other cultures, their cognitive flexibility, their ability to view things from a multiple perspective and their global competence exerted moderate effects on RPOC. Gender and school climate exerted small negative effects, while global mindedness, perceived parents’ emotional support and sense of belonging exerted small, but significant, effects. Overall, the model accounted for 40% of the variance in RPOC. This suggests that additional variables need to be identified to gain a fuller understanding of the influences on Hong Kong students’ intercultural behavior.